Improving Writing Skills of Recount Text through Quantum Learning Model with Concept Map Technique - Sariah Sariah; Yumna Rasyid; Herlina herlina (English Department - University of Sultan Ageng Tirtayasa, 2018)
Abstract: The aims of this research are: 1) To describe the process of learning in recount text writing skill through quantum learning model by mind mapping technique, 2) To describe the increasing of recount text writing skill through quantum learning model by mind mapping technique. Design in this action research use three cycle. Data take from observation, test, and documentation. Data was analysis as descriptive quantitative. The result show that 1) Students activity in learning process have increased significantly from several cycle, 2) Writing skill of recount text students have significantly increasing after following quantum learning model by mind mapping technique. The means value that students got are; the first cycle is 66.93, the second cycle is 76.53, and the third cycle is 84.67%.Keyword: mind mapping, quantum learning, writing skill, recount text